Studi Etnobotani Penggunaan Surawung di Desa Cinunuk, Kecamatan Cileunyi, Kabupaten Bandung, Jawa Barat (International Forum of Researchers and Lecturers, 2024)
Ethnobotany is the field of science that explains how humans interact with the plants around them. The most common use of plants is as food and medicine. Surawung or basil leaves are one of the plants commonly used as food. The purpose of this study was to determine the use of surawung other than as food. Samples were taken using snowball sampling method in Cinunuk Village. From 30 respondents, about 17% of them used surawung for their health reasons. It is known that surawung leaves have antibacterial bioactive content. Even so, most respondents did not know in detail about the benefits of surawung leaves.